The assessment of white blood corpuscles by geometric-morphometric analysis after the application of calcium aluminate and calcium silicate dental cements in wistar rats - Muhamed KATICA; Zurifa AJANOVIĆ; Aida BEŠIĆ; Ognjenka JANKOVIĆ; Emina DERVIŠEVIĆ; Nedžad HADŽIOMEROVIĆ; Faruk TANDIR 5 Smiljana PARAŠ; Amina LUČKIN; Vukoman JOKANOVIĆ (Kafkas Universitesi Veteriner Fakültesi Dergisi)
The aim of the research was to determine possible changes in the morphology of cells of the leukocyte order of peripheral blood, using geometric morphometric tests, after the application of calcium-aluminate and calcium-silicate cements to the dental pulp in rats. The study included 27 Wistar rats, divided into an experimental group (n=18) and a control group (n=9). Trepanation of the tip of the pulp cavity was performed, and placement of calcium-aluminate and calcium-silicate dental cements directly on the pulp. Peripheral blood samples were collected by vena caudalis puncture, with the aim of making blood smears. In the tpsUtil program, two-dimensional models of the examined leukocytes were created and they were converted into tps files, on which sixteen specific points were marked in the tpsDig program. We analyzed their shape in the MorphoJ program. The results of discriminant functional analysis determined that there was a statistically significant difference in the shape of the lymphocytes between the experimental animals, to which dental cements were applied, compared to the lymphocytes from the control group. Morphological differences were determined between the lymphocytes to which calcium aluminate and calcium silicate were applied. The results indicate that there were statistically significant morphological differences between these two groups of lymphocytes (P=0.02). The results obtained indicate the possibly unfavorable influence of the tested dental cements, especially calcium silicate, on leukocytic cells.